Funding and Expenditure of a Sample of Community-based Organizations in Kenya, Nigeria, and Zimbabwe - Krivelyova, Anya (Taylor and Francis, 2013)
Over the last decade, international donors, technical specialists, and governments have come to recognize the potential of community-based organizations (CBOs) in the fight against HIV/AIDS. Recent empirical studies suggest that community engagement, including the involvement of CBOs, adds value to the national response to HIV/AIDS. With the emerging evidence of the effectiveness of engaging communities in the fight against AIDS, it is crucial to understand the economic dimension of community engagement. This article provides an analysis of funding and expenditure data collected from CBOs in three African countries: Kenya, Nigeria, and Zimbabwe. It presents descriptive information regarding CBO funding and expenditure and examines the factors associated with the total amount of funds received and with the proportions of the funds allocated to programmatic activities and program management and administration. An average CBO in the sample received US$29,800 annually or about US$2480 per month. The highest percentage of CBO funding (37%) came from multilateral organizations. CBOs in the sample spent most of their funds (71%) on programmatic activities including provision of treatment, support, care, impact mitigation, and treatment services.